2023
DOI: 10.1021/acs.inorgchem.2c02868
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Luminescent Dual Responses of Photochromic Hexaazamacrocyclic Lanthanide Complexes

Abstract: Herein, hexaazamacrocyclic ligand LN6 was employed to construct a series of photochromic rare-earth complexes, [Ln(LN6)(NO3)2](BPh4) [1-Ln, Ln = Dy, Tb, Eu, Gd, Y; LN6 = (3E,5E,10E,12E)-3,6,10,13-tetraaza-1,8(2,6)-dipyridinacyclotetradecaphane-3,5,10,12-tetraene]. The behavior of photogenerated radicals of hexaazamacrocyclic ligands was revealed for the first time. Upon 365 nm light irradiation, complexes 1-Ln exhibit photochromic behavior induced by photogenerated radicals according to EPR and UV–vis analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 99 publications
2
18
0
Order By: Relevance
“…Complexes (1) , (3) , (4) , and (5) were all lower than the theoretical saturation value (10, 18, 20, and 18 μ B , respectively), while complex (2) was higher than the theoretical saturation value of the Dy­(III) ion (20 μ B ). The M and H / T curves of complex (1) tend to be saturated at different temperatures, which is consistent with the magnetization of Ising-like Dy­(III) ion with ground-coupled pole m J at high magnetic fields, and these magnetic dynamics may be due to the anisotropy and low excited states, and the existence of SMM properties is also revealed. , However, the M and H / T curves of complexes (2–5) do not overlap at different temperatures, implying the existence of low excited states caused by crystal field splitting and/or magnetic coupling. …”
Section: Resultssupporting
confidence: 66%
“…Complexes (1) , (3) , (4) , and (5) were all lower than the theoretical saturation value (10, 18, 20, and 18 μ B , respectively), while complex (2) was higher than the theoretical saturation value of the Dy­(III) ion (20 μ B ). The M and H / T curves of complex (1) tend to be saturated at different temperatures, which is consistent with the magnetization of Ising-like Dy­(III) ion with ground-coupled pole m J at high magnetic fields, and these magnetic dynamics may be due to the anisotropy and low excited states, and the existence of SMM properties is also revealed. , However, the M and H / T curves of complexes (2–5) do not overlap at different temperatures, implying the existence of low excited states caused by crystal field splitting and/or magnetic coupling. …”
Section: Resultssupporting
confidence: 66%
“…, 2,4,6-tri(4-pyridyl)-1,3,5-triazine and hexaazamacyclic ligands) as guests or chelating ligands is helpful to construct magneto-optical multi-switches with photochromic properties. 80 When employing organic radicals with magnetic bistability ( i.e. , dithiadiazolyl radicals 81 ), we can exploit novel systems that exhibit a hysteretic response to various external stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…A few research groups have addressed this challenge using luminescent Ln-SMMs. 129,[254][255][256][257][258] They mainly explored a strategy that relies on the incorporation of photo-responsive organic components into the system, which, through photo-chemical reactions, causes structural changes that affect both luminescence and magnetic properties. Wang et al reported a family of coordination-chain-based supramolecular compounds, [Ln III 3 (H-HEDP) 3 (H 2 -HEDP) 3 ]Á2(H 3 -TPT)Á(H 4 -HEDP)Á 10H 2 O (Ln = Dy, Gd, Y; HEDP = hydroxyethylidene diphosphonate; TPT = 2,4,6-tri(4-pyridyl)-1,3,5-triazine), that exhibit reversible roomtemperature photochromism (both in absorption and emission) and photomagnetism (Fig.…”
Section: Photo-switching Of Luminescent Lanthanide Smmsmentioning
confidence: 99%